In vivo and in vitro comparison of the effects of propofol, midazolam and fentanyl on the 'NK' cells of human immune system [Propofol, midazolam ve fentanilin insan bagisiklik sisteminde 'NK' hucrelerine etkisinin in vivo ve in vitro arastirilmasi] - (:unkn) unknown (My University, 1998)
This study was designed to assess the effects of intravenous anaesthetic drugs propofol, midazolam and fentanyl on the 'natural killer' cell (NK) activity (cytotoxicity) of human immunologic system in vivo and in vitro. 8 patients scheduled for laparoscopic cholecystectomy aged between 18-68 years were included in the study and allocated into two groups (n=4) after the written informed consent and the approval of hospital Ethics Committee. In Group I; anaesthetic induction was performed with propofol 2 mg/kg and fentanyl 5 μg/kg IV and anaesthesia was maintained with the intravenous infusion of propofol 10 mg/kg/h and 6 mg/kg/h fentanyl 3 mg/kg/h. In group II; induction was performed with midazolam 0.2 mg/kg and fentanyl 5 μg/kg IV and the maintenance was performed with midazolam 0.15 kg/kg/h and fentanyl 3 μg/kg/h with IV infusion. Before anaesthetic induction, 60 minutes after the induction and at the 60th minute after the surgery, peripheral blood samples from patients were collected. Target cells were radioactive labeled K-562 cells. NK cytotoxicity was measured as; cpm (test) - cpm (med) / cpm (max) - cpm (med) In conclusion, in clinical concentrations with 90 minutes per period of anaesthesia none of the drugs mentioned above had an inhibitory effect on NK cell activity neither in vivo nor in vitro.
Keywords: Fentanyl; Immunity; Midazolam; Propofol